Pneumothorax in a young man with anorexia nervosa. Issue 9 (19th May 2016) - Loung, Robert P.Y.; Cooney, Megan; Fallon, Erica M.; Langer, Jacob C.; Katzman, Debra K.
ABSTRACT: Primary spontaneous pneumothorax (PSP) is defined as a pneumothorax that occurs in the absence of an external cause in an individual without underlying generalized lung disease. A number of factors are important and should be carefully considered in the pathogenesis of PSP. This is the first case report of a PSP in a severely malnourished adolescent male with anorexia nervosa (AN) who was involved in excessive physical activity. Clinicians caring for adolescents with AN and vigorous exercise need to be aware of the risk factors associated with the development of a PSP. © 2016 Wiley Periodicals, Inc.(Int J Eat Disord 2016; 49:895–898)